Comparison of Clinical and Pathological Diagnoses in Cats and Dogs. Issue 2 (February 2017) - Schertenleib, T.I.; Pospischil, A.; Hässig, M.; Kircher, P.R.; Hilbe, M.
Summary: The comparison of clinical ante-mortem and pathological post-mortem diagnoses is a prerequisite for quality control, but is rarely done in veterinary medicine. This study reports the occurrence and concurrence of clinical and pathological diagnoses linked to death in 1, 000 cats and 1, 000 dogs examined and subjected to necropsy examination at the University of Zurich, Switzerland. Potential factors influencing the correlation between diagnoses were examined retrospectively. In 5.8% of cats and 5.2% of dogs no diagnosis was made; in 2.6% and 3.8% of cases only a clinical, and in 17.8% and 11.2%, respectively, only a pathological diagnosis was available. Of the 73.8% of cats and 79.8% of dogs with both diagnoses present, 38.3% and 36.2% were in agreement, while there was disagreement in 17.9% and 16.0%, respectively. The remaining cases (43.8% and 47.8%) had different levels of further diagnostic procedures following necropsy examination. In both species, the manner of death, the clinical discipline submitting the animal for necropsy examination and the quality of the necropsy submission request, as well as the timespan between death and necropsy examination in dogs, proved to influence the concurrence between diagnoses. In contrast, the organ system affected and the type of disease entity were, for both species, the most influential factors in the concurrence of diagnoses. Therefore, in veterinary medicine, even in times of improving diagnostic abilities, necropsy examination still reveals important information for quality control and education.